'Mathematics Achievement in Crisis': Modelling the Influence of Teacher Knowledge and Experience in Senior High Schools in Ghana - Ansah Joseph Kweku; Quansah Frank; Nugba Regina Mawusi (De Gruyter, 2020)
Mathematics achievement in senior high schools (SHS) in Ghana is not encouraging and this has become a concern for major stakeholders. Several studies have been conducted to provide information to understand the issue of poor mathematics achievement. Of all the studies, areas regarding the joint influence of experience, pedagogical content knowledge (PCK) and subject matter knowledge (SMK) have been less explored in Ghana. In this study, the interplay among these variables is examined in an attempt to explain the variances in students' mathematics achievement. To achieve this purpose, 210 SHS teachers and 8,400 students in SHS across the country were surveyed and subsequently administered tasks on algebra taking into consideration the variables of interest. The study revealed that teacher knowledge and teaching experience significantly influenced students' mathematics achievement. It was discovered that PCK had a significant indirect effect on students' mathematics achievement through teachers' SMK. The findings also showed that experience did not significantly moderate the relationship between teachers' SMK and students' mathematics achievement. The study, based on the outcome, made conclusions and recommendations for practice. Suggestions for the implementation of future studies were also highlighted.